Psychiatry as a vocation. - Perales Cabrera, Alberto (2015)
Objective: To describe and delimit the psychiatric vocation process and its associated factors. Design: Transversal, qualitative, descriptive and comparative study of cases. Methodology: Previous informed consent in depth audio-recorded interviews were carried out in two groups selected by criteria of heterogeneity, 45 psychiatrists currently in practice and 61 residents in psychiatry. Results and conclusions: Psychiatric vocation includes several dimensions. It considers the person as an integral being, showing strong interest on the psychological part of the patient and a need to reduce the suffering caused by mental illness. In the group of psychiatrists, the psychiatric vocation showed itself as more consolidated and genuine. In the group of residents, psychiatric vocation appeared as a weak and in some cases inexistent process. Several residents chose psychiatry as a career on account of personal convenience because they did not reach vacancy in their preferred specialty.